Jingles Identifying a Radio Station as an Important Element of a Radio Programme: Analysis of the Production Process - Szydłowska, Magdalena; Doliwa, Urszula; Piasecka, Katarzyna; Podbielska, Agnieszka; Kobak, Karolina; Wiśniewska, Marta (Media - Culture - Social Communication, 2019)
Jingles are important elements of radio programs and require much attention and effort. The authors have decided to check what the process of the production of radio jingles looks like and how this process is related to the format and character of the broadcasting institutions. In this study, several aspects of the production were taken into account, such as: the place, the authorship and the applied concept. The basis of the studies were interviews with representatives of various types of radio stations: public, commercial and non-commercial; local, regional and national radio programs were also taken into consideration.